1989
DOI: 10.2337/diacare.12.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Glucose and Lowered Triglyceride Levels From Omega-3 Fatty Acid Supplementation in Type II Diabetes

Abstract: We studied the effect of omega-3 fatty acids (omega 3FA) on glucose homeostasis and lipoprotein levels in eight type II (non-insulin-dependent)-diabetic subjects ingesting 8 g/day omega 3FA for 8 wk as marine-lipid concentrate capsules. After omega 3FA supplementation, fasting plasma glucose levels increased 22% (P = .005) and meal-stimulated glucose increased 35% (P = .036). The percentage of glucose elevation correlated with percentage ideal body weight (r = .73, P = .04). No significant changes were seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(53 citation statements)
references
References 17 publications
7
44
0
1
Order By: Relevance
“…With a daily intake of 7-8 g/day of fish oil, the mean reduction in plasma triacylglycerol after 3 months of fish oil consumption was 29.1 and 29.9 % for low and high P/S participants, respectively. This observation is comparable to the reduction in triacylglycerol levels observed after NIDDM patients received 8 g of w 3 fatty acids for 8 weeks [26]. In the present study, ingestion of 18:3w3 by NIDDM patients did not reduce plasma triacylglycerol levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With a daily intake of 7-8 g/day of fish oil, the mean reduction in plasma triacylglycerol after 3 months of fish oil consumption was 29.1 and 29.9 % for low and high P/S participants, respectively. This observation is comparable to the reduction in triacylglycerol levels observed after NIDDM patients received 8 g of w 3 fatty acids for 8 weeks [26]. In the present study, ingestion of 18:3w3 by NIDDM patients did not reduce plasma triacylglycerol levels.…”
Section: Discussionsupporting
confidence: 88%
“…Research results suggest that insulin sensitivity is increased after the addition of 3 g of w 3 fatty acid to the diet of NIDDM patients for 8 weeks [25]. In other NIDDM patients, ingesting 8 g/day of w 3 fatty acids reduced VLDL cholesterol and plasma triacylglycerol levels by 56 and 42 %, respectively [26]. The LDL and HDL cholesterol level was not affected; however, the w 3 fatty acid supplementation increased both the fasting and postprandial plasma glucose level.…”
Section: : 45-52]mentioning
confidence: 99%
“…Some studies have observed an increase in blood glucose in type 2-diabetes after fish oil supplementation (Friday et al, 1989;Vessby et al, 1992). However, a newly published metaanalysis based in 12 studies conducted on type 2 diabetic patients concluded that fish oil did not raise either blood glucose level or HbA 1c (Montori et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The marine fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) have been associated with diverse effects on glucose metabolism. Some studies have observed adverse associations to insulin sensitivity [5,[9][10][11], although other studies have not [12].…”
mentioning
confidence: 99%